2017
DOI: 10.4174/astr.2017.93.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-released mixture of vascular endothelial growth factor 165 and fibrin glue strengthens healing of ileal anastomoses in a rabbit model with intraperitoneal infection

Abstract: PurposeTo investigate the effects of a sustained-released mixture of vascular endothelial growth factor 165 (VEGF165) and fibrin glue (FG) local administration on postoperative rabbit ileal anastomoses.MethodsOne hundred twenty-eight male and female New Zealand white rabbits underwent intraperitoneal infection subsequent ileal anastomosis surgery were divided randomly into 4 groups, including 32 animals in each, applied with saline solution, FG, rhVEGF165 and a mixture of rhVEGF165 with FG (VEGF + FG) on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It is also the key reason why we chose the MSCs secretome as a therapeutic agent in our study. We harvested the secretome from the culture medium of MSCs and subsequently detected several growth factors that have been reported to promote surgical anastomotic healing, such as FGF-2, VEGF, and IGF-1 (Oines et al, 2014;Li et al, 2017), which are essential key factors involved in tissue repair and regeneration. In vitro studies also found that the MSCs secretome accelerated the viability of key cells involved in tissue repair in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also the key reason why we chose the MSCs secretome as a therapeutic agent in our study. We harvested the secretome from the culture medium of MSCs and subsequently detected several growth factors that have been reported to promote surgical anastomotic healing, such as FGF-2, VEGF, and IGF-1 (Oines et al, 2014;Li et al, 2017), which are essential key factors involved in tissue repair and regeneration. In vitro studies also found that the MSCs secretome accelerated the viability of key cells involved in tissue repair in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies in the field of intestinal anastomotic healing have employed fibrin glue as the scaffold to deliver exogenous growth factors VEGF (Li et al, 2017), and growth hormone (Li et al, 2007;Wang et al, 2009), demonstrating fibrin glue's application potential as a sustained-release carrier for growth factors. However, compared with MSCs secretome therapy, this kind of mono-factor therapy has significant disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the approach of their pharmacological administration could be particularly promising for anastomoses of questionable perfusion. Still, there is very few preclinical, yet positive evidence on administration of EPO and VEGF to improve anastomotic healing [ 11 , 23 , 27 ]. Lack of known side-effects of short time treatment would allow perioperative treatment.…”
Section: Experimental Approaches For Induction Of Anastomotic Healingmentioning
confidence: 99%